Addition of Turmeric Curcumin Extract in Feed to Improve Non-Specific Immunity of Pangasius hypothalmus that is Maintained in Cages - Andesra, Andesra; Riauwaty, Morina; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on June until August 2018 in Experimental Pond and Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine Science, University of Riau, Pekanbaru. The purpose of this study was to determine the effect of adding turmeric curcumin extract and the best dosage of turmeric curcumin extract which was added to the feed to enhance the non-specific immune system of Pangasius hypothalmus which is maintained in cages. The method used is the experimental method with a Completely Randomized Design (CRD) of one factor 4 level of treatment. Each treatment, namely: P0: Feeding without addition of turmeric curcumin extract, P1: Adding turmeric curcumin extract in feed at a dose of 0.5 g / kg, P2: Adding turmeric curcumin extract in feed at a dose of 0.7 g / kg , P3: Addition of curcumin extract in feed at a dose of 0.9 g / kg. The test fish used was Pangasius hypothalmus with a size of 7-8 cm as many as 600 tails. The parameters measured are; total leukocytes, leukocyte values, leukocyte differentiation, phagocytic index, absolute weight growth, survival rate and water quality measurements. The results obtained from the study, namely there is the effect of giving turmeric curcumin extract in feed with the best dose is 0.9 g / kg, which is indicated by a total leukocyte of 9,41x104 cells/mm3, leukocyte value of 1,67%, lymphocytes value 80,67 %, neutrophils 7.33%, monocytes 12.00%, phagocytosis index 29.67%, absolute weight growth 31.67% and survival rate 99.33%. Keywords: Leukocytes, Pangasius hypothalmus, Turmeric curcumin extract